Răspuns:
Explicație pas cu pas:
Descompuneți în factori:
a) x²+4xy+3y²=x²+4xy+4y²-y²=(x+2y)²-y²=(x+2y+y)(x+2y-y)=(x+3y)(x+y)
b) x²-3xy+2y²=x²-2xy+y²-xy+y²=(x-y)²-y(x-y)=(x-y)(x-y-y)=(x-y)(x-2y)
c) 3x²-7xy+4y²=4x²-x²-8xy+xy+4y²=4x²-8xy+4y²-x²+xy=4(x²-2xy+y²)-x(x-y)= 4(x-y)²-x(x-y)=(x-y)(4x-4y-x)=(x-y)(3x-4y)
d) 2x²+7xy-9y²=2x²+7xy-7y²-2y²=2x²-2y²+7xy-7y²=2(x²-y²)+7y(x-y)=
2(x-y)(x+y)+7y(x-y)=(x-y)(2x+2y+7y)=(x-y)(2x+9y)
e) x²+xy-6y²=x²-4y²+xy-2y²=(x²-4y²)+y(x-2y)=(x-2y)(x+2y)+y(x-2y)=
(x-2y)(x+2y+y)=(x-2y)(x+3y)
f) 2x²+5xy+3y²=2x²+2xy+3xy+3y²=2x(x+y)+3y(x+y)=(x+y)(2x+3y)
Au fost folosite formulele de calcul prescurtat:
a²-b²=(a+b)(a-b)
a²+2ab+b²=(a+b)²
a²-2ab+b²=(a-b)²